One More Thing on the Subject: Generating Chaos via x|x|[sup.a−1], Melnikov’s Approach Using Simulations - Kyurkchiev, Nikolay; Iliev, Anton; Kyurkchiev, Vesselin; Rahnev, Asen (Mathematics (Basel), 2025)
In this article, we propose a new hypothetical differential model with many free parameters, which makes it attractive to users. The motivation is as follows: an extended model is proposed that allows us to investigate classical and newer models appearing in the literature at a “higher energy level”, as well as the generation of high–order Melnikov polynomials (corresponding to the proposed extended model) with possible applications in the field of antenna feeder technology. We present a few specific modules for examining these oscillators’ behavior. A much broader Web-based application for scientific computing will incorporate this as a key component.